2017
DOI: 10.1128/jvi.00344-17
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Overcomes Polyamine Depletion by Mutation of nsP1 and the Opal Stop Codon To Confer Enhanced Replication and Fitness

Abstract: Polyamines, which are small positively charge molecules present in all cells, play important roles in the replication of DNA and RNA viruses. Chikungunya virus (CHIKV) relies on polyamines for translation of the viral genome upon viral entry, and pharmacological depletion of polyamines limits viral replication. However, the potential development of antiviral resistance necessitates a better understanding of how polyamines function and can be targeted via compounds that alter polyamine levels. We have isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Both R171Q and opal524R had been previously reported in CHIKV isolates such as MADOPY1, StBI and StVE (GenBank accession numbers KP003808.1, KP003811.1, and KP003810.1 respectively) which all had been passaged in cell culture prior to sequencing [33]. The mutation opal524R in the nsP3-coding region was reported also by Mounce et al in the context of resistance selection against the compound DFMO [34], alongside with other nsP mutations. In the case of CHIKV and other alphaviruses (SFV, ONNV), evolutionary pressures have maintained both variants (stop and arginine codon) as it offers a fitness advantage when switching between vertebrate and invertebrate hosts [35][36][37].…”
Section: Suramin-resistant Chikv Variants Acquired Mutations In the Ementioning
confidence: 64%
“…Both R171Q and opal524R had been previously reported in CHIKV isolates such as MADOPY1, StBI and StVE (GenBank accession numbers KP003808.1, KP003811.1, and KP003810.1 respectively) which all had been passaged in cell culture prior to sequencing [33]. The mutation opal524R in the nsP3-coding region was reported also by Mounce et al in the context of resistance selection against the compound DFMO [34], alongside with other nsP mutations. In the case of CHIKV and other alphaviruses (SFV, ONNV), evolutionary pressures have maintained both variants (stop and arginine codon) as it offers a fitness advantage when switching between vertebrate and invertebrate hosts [35][36][37].…”
Section: Suramin-resistant Chikv Variants Acquired Mutations In the Ementioning
confidence: 64%
“…A recent study by Ashbrook et al found that inhibitors of sodium-potassium ATPases antagonize CHIKV replication and that drug-resistant variants often contain mutations in the opal termination codon ( 44 ). Drug-resistant variants containing the Opal524R mutation were also obtained when CHIKV was instead passaged in the presence of difluoromethylornithine (DFMO), a drug that inhibits polyamine biosynthesis and thereby restricts viral replication ( 45 , 46 ). Interestingly, the Opal524R mutant did not replicate as well as the parental strain in either Aedes albopictus mosquitos or zebrafish, but when combined with additional drug-resistant mutations, the Opal524R mutation enhances replication in vivo ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug-resistant variants containing the Opal524R mutation were also obtained when CHIKV was instead passaged in the presence of difluoromethylornithine (DFMO), a drug that inhibits polyamine biosynthesis and thereby restricts viral replication ( 45 , 46 ). Interestingly, the Opal524R mutant did not replicate as well as the parental strain in either Aedes albopictus mosquitos or zebrafish, but when combined with additional drug-resistant mutations, the Opal524R mutation enhances replication in vivo ( 46 ). Although these drug-resistant variants have not, to our knowledge, been tested for virulence in a mouse model, our results suggest that these viruses would cause less tissue damage than the parental virus.…”
Section: Discussionmentioning
confidence: 99%
“…An additional mutation of the opal stop codon to an arginine codon (*524R) at the end of the nsP3-coding sequence further increased resistance, but this appeared to be a nonspecific effect (cell culture adaptation). In an independent study with the polyamine inhibitor difluoromethylornithine (DFMO), Mounce et al found that the G230R mutation in CHIKV nsP1 contributes to resistance to polyamine depletion (37). This might reflect the interconnectedness of pathways linked to methionine metabolism and polyamine biosynthesis (17,38).…”
Section: Discussionmentioning
confidence: 99%